Survey of workplace stressors among Hungarian elite athletes - Resperger, Viktória; Kapros, Anikó; Berki, Tamás (Frontiers in Psychology, 2025)
IntroductionPeople working in sports, particularly athletes, are vulnerable to workplace stressors. These stressors can arise from various factors and significantly impact an individual’s mental, physical, and emotional well-being. This ongoing research maps out the workplace stressors affecting professional Hungarian athletes involved in competitive sports. The study identifies work-related factors that may influence athletes’ stress levels. It highlights the parallels between traditional workplace stressors and stressors that affect athletes and shows these stressors across different genders, types of sports, and competition levels. The results also compare the stressors faced by various kinds of sports (such as individual versus team sports).MethodsThe research was conducted in two stages. A questionnaire prepared as a starting point was designed for a quantitative data collection method using questionnaires. A qualitative preparatory phase was included to refine the questionnaire. The study emphasizes the significance of work-related stress amongst athletes by explicitly examining workplace stressors in sports using an established model.ResultsThe findings show ten factors and three second-order factors for measuring work-related stress among athletes. The research also identifies differences between how male and female athletes perceive work-related stress. Furthermore, the results indicate that individual athletes experience higher work-related stress levels than team sports.DiscussionOur research highlights the importance of recognizing and addressing the various stressors athletes face throughout their careers.